Antifeedant Potential of Geranylacetone and Nerylacetone and Their Epoxy-Derivatives against Myzus persicae (Sulz.) - Anna Wróblewska-Kurdyk; Katarzyna Dancewicz; Anna Gliszczyńska; Beata Gabryś (Molecules, 2022)
Geranylacetone and nerylacetone are natural sesquiterpenoids, which play various roles in plant-insect interactions, including the deterrent and repellent effects on herbivores. The structural modifications of natural compounds often change their biological activities. The aim of the study was to evaluate the effect of geranylacetone, nerylacetone and their epoxy-derivatives on the probing and settling behavior of Myzus persicae (Sulz.) (Hemiptera: Aphididae). The no-choice test using the Electrical Penetration Graph (EPG) technique showed that the probes before the first phloem phase were usually shorter than 3 min, which means that they were terminated within the epidermis and/or outer layers of mesophyll. This resulted in a tendency to delay the initiation of the phloem phase in aphids, which reflects a weak preingestive deterrent activity of the studied compounds at the level of non-vascular tissues. Most M. persicae showed bouts of sustained phloem sap ingestion. However, the 24-h free-choice test demonstrated that aphids did not settle on the leaves treated with geranylacetone, nerylacetone, and their epoxy-derivatives. The refusal to settle after the consumption of phloem sap on treated plants indicated that the studied compounds had postingestive deterrent activity. The epoxidation of geranylacetone and nerylacetone did not evoke significant changes in their activity profiles.